Design and Synthesis of Supramolecular Phosphatases Formed from a Bis(Zn2+‐Cyclen) Complex, Barbital‐Crown‐K+ Conjugate and Cu2+ for the Catalytic Hydrolysis of Phosphate Monoester. Issue 13 (29th January 2021) - Rahman, Akib Bin; Okamoto, Hirokazu; Miyazawa, Yuya; Aoki, Shin
Abstract: The development of artificial mimics of natural enzymes such as hydrolases and phosphatases is one of the great challenges in bioorganic and bioinorganic chemistry and related sciences. Supramolecular strategies are one of the useful methods to construct artificial catalysts as mimics of natural enzymes and to understand their reaction mechanisms. Herein, we report on the formation of amphiphilic supramolecular phosphatases by the 2 : 2 : 2 self‐assembly of a bis(Zn 2+ ‐cyclen) complex (cyclen=1, 4, 7, 10‐teraazacyclododecane) containing a 2, 2′‐bipyridyl (bpy) linker and one long alkyl chain (Zn2 L 3 ), 5, 5‐diethylbarbituric acid (Bar) derivative functionalized with 1‐aza‐18‐crown‐6 ether and Cu 2+ in a two‐phase solvent system (CHCl3 /H2 O). We hypothesized that crown ether moiety of the Bar‐crown ether conjugate would form complexes with alkaline ions and other metal ions such as Li +, Na +, K +, Rb +, Mg 2+ and La 3+ in organic phase to mimic the Mg 2+ found as the third metal ion in the active site of alkaline phosphatase (AP). The results indicate that the 2 : 2 : 2 : 4 complexes of Zn2 L 3, a Bar block equipped with the 18‐crown‐6 ether, Cu 2+ and alkaline metal are constructed in a two‐phase solvent system. The resulting complexes have a higher hydrolysis activity for mono(4‐nitrophenyl)phosphate (MNP) in the presence of K + than that in the presence of Li +, Na +, Rb +, Mg 2+ and La 3+ and a greater hydrolysis activity than our previous supermolecules having no crown ether part, suggesting that crown ether‐K + complex located in close proximity to the Cu2 ( μ ‐OH)2 core contributes to the acceleration of the MNP hydrolysis. Abstract : We report on the design and synthesis of supramolecular complexes formed by the 2 : 2 : 2 self‐assembly of an amphiphilic zinc(II)‐cyclen complex containing one long alkyl chain (Zn2 L 3 ), a barbital derivative functionalized with crown ether‐metal (Li +, Na +, K +, Rb +, Mg 2+, La 3+ ) complex and Cu 2+ and their catalytic activity for the hydrolysis of mono(4‐nitrophenyl)phosphate (MNP) in a two‐phase solvent system.